Electromyographic and kinematic analysis during treadmill running protocol - Fraga, C. H W [UNESP]; Bianco, R.; Crema, A. A S; Castro, A. [UNESP]; Serrão, J. C.; Amadio, A. C.; Gonçalves, M. [UNESP] (My University, 2014)
Aim. The objective of this study was to compare electromyographic signal (EMG), stride length (SL) and stride frequency (SF) in three different speeds during an incremental running protocol on a treadmill. Methods. Eleven male recreational runners performed an incremental running protocols on treadmill with an initial speed of 10 km/h and increments of 1 km/h every three minutes, with 30s intervals between each speed increase, up to exhaustion. The EMG signal was obtained of theiliocostalis lumborum (IC), rectus femoris (RF), vastus lateralis (VL), vastus medialis (VM), biceps femoris (BF), tibialis anterior (TA) and gastrocnemius lateralis (GL) muscles. The RMS (Root Mean Square) values of each muscle and the kinematic data (SL and SF) were calculated considering the mean of the ten last strides, and compared in the three intensities: 60%, 80% and 100% of the maximal speed (Vmax). Results. The RMS values corresponding to 100% were greater than 60% and 80% for IC, RF, VL, BF and GL, and those corresponding to 80% were greater than 60% for IC, RF and GL (P<0.05). For TA the values corresponding to 100% were only greater than 60% of the Vmax (P<0.05). The SL and SF values corresponding to 100% were greater than 60% and 80%, and 80% were greater than 60% (P<0.05). Conclusion. The EMG signal showed higher values with increasing speed, but this has not been a behavioral pattern to the muscles analyzed in this study. Furthermore, the increase in running speed was achieved through both SL and SF.
Keywords: Athletic performance; Electromyography; Fatigue; Running